Sources of information about complementary and alternative medicine commonly used by oncology patients and healthcare professionals - Aleksandar, Racz; Vanja, Vasiljev; Tomislav, Rukavina; Marija, Hošnjak Ana; Ljerka, Armano (Edelweiss Applied Science and Technology, 2025)
Complementary and Alternative Medicine (CAM) is increasingly utilized in oncology care; however, significant disparities exist regarding the trusted sources of CAM information among oncology patients and healthcare professionals. This study aimed to systematically evaluate these information sources, their credibility, and their influence on medical decision-making. A cross-sectional study was conducted at the Sisters of Mercy University Hospital Center in Zagreb from November 2022 to May 2023. The sample consisted of 832 respondents, comprising 411 oncology patients and 421 healthcare professionals, including 100 physicians, 321 nurses, and technicians. Data were collected using a survey questionnaire based on modified CHBQ and IMAQ instruments. Descriptive and inferential statistical methods were applied, including one-way analysis of variance (ANOVA) and Tukey's test to identify differences among groups. The most common sources of CAM information for patients were family and friends (82.6%), while healthcare professionals were more inclined to use the internet and media (61.4%). Statistically significant differences in attitudes were identified between patients and healthcare professionals regarding their information sources (p < 0.05). These findings underscore a pressing need for standardized, evidence-based complementary and alternative medicine (CAM) education that is tailored to both patients and healthcare providers. Addressing these disparities through targeted educational interventions could enhance informed decision-making, reduce misinformation, and optimize the delivery of integrative oncology care. Future research should focus on developing verified CAM information frameworks to ensure a more consistent and scientifically grounded approach in oncology settings.